Effects of Surgical Factors on Cartilage Can Be Detected Using Quantitative Magnetic Resonance Imaging After Anterior Cruciate Ligament Reconstruction. (April 2017) - Amano, Keiko; Li, Alan K.; Pedoia, Valentina; Koff, Matthew F.; Krych, Aaron J.; Link, Thomas M.; Potter, Hollis; Rodeo, Scott; Li, Xiaojuan; Ma, C. Benjamin; Majumdar, Sharmila
Background: Quantitative magnetic resonance (qMR) can be used to measure macromolecules in tissues and is a potential method of observing early cartilage changes in the development of posttraumatic osteoarthritis. Hypothesis/Purpose: We hypothesized that specific patient and surgical factors affecting cartilage matrix composition after anterior cruciate ligament (ACL) reconstruction (ACLR) can be detected using T1ρ and T2 relaxation times. Our purpose was to demonstrate this ability in a multicenter feasibility study. Study Design: Case series; Level of evidence, 4. Methods: A total of 54 patients who underwent ACLR underwent bilateral MRI at baseline before surgery and 6 months postoperatively. Operative findings were recorded. T1ρ and T2 relaxation times were calculated for 6 cartilage regions: the medial femur, lateral femur, medial tibia, lateral tibia, patella, and trochlea. A paired t test compared relaxation times at baseline and 6 months, univariate regression identified regions that influenced patient-reported outcome measures, and analysis of covariance was used to determine the surgical factors that resulted in elevated relaxation times at 6 months. Results: The injured knee had significantly prolonged T1ρ and T2 relaxation times in the tibiofemoral compartment at baseline and 6 months but had shorter values in the patellofemoral compartment compared with the uninjured knee. Prolonged T1ρ and T2 times at 6 months were noted for both the injured and uninjured knees. At 6 months, prolongation of T1ρ and T2 times in the tibial region was associated with lower patient-reported outcome measures. ACLR performed within 30 days of injury had significantly shorter T1ρ times in the tibial regions, and lateral meniscal tears treated with repair had significantly shorter T1ρ times than those treated with excision. Conclusion: Prolonged relaxation times in multiple regions demonstrate how the injury affects the entire joint after an ACL tear. Changes observed in the uninjured knee may be caused by increased loading during rehabilitation, especially in the patellofemoral articular cartilage and distal femur. Relaxation times in the tibial regions may be predictive of patient symptoms at 6 months. These same regions are affected by surgical timing as early as 30 days after injury, but this may partially be reflective of the severity of the preoperative injury and the choice of treatment of meniscal tears.